1963
DOI: 10.1159/000129779
|View full text |Cite
|
Sign up to set email alerts
|

A Family Showing Transmission of a D/D Reciprocal Translocation and a Case of Regular 21-Trisomic Down’s Syndrome

Abstract: A family showing transmission of a D/D type translocation is reported. The chromosomes involved are probably Nos. 13 and 15 (Denver). Attempts to localize a number of marker genes in relation to the centromere of the translocated chromosome were unsuccessful. The propositus in this family was a case of regular (21-trisomy) Down’s syndrome (Mongolism). The possible association between non-disjunction and the translocation is discussed both in relation to the present family and others in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

1967
1967
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…There were some reports about the occurrence of regular 21 trisomy from familial D/D translocation (Hamerton et al, 1963;Yunis et al, 1964;Zergollern et al,, 1964). Dutrillaux and Lejeaune (1970) analyzed 67 families with familial t(DqDq).…”
Section: Discussionmentioning
confidence: 99%
“…There were some reports about the occurrence of regular 21 trisomy from familial D/D translocation (Hamerton et al, 1963;Yunis et al, 1964;Zergollern et al,, 1964). Dutrillaux and Lejeaune (1970) analyzed 67 families with familial t(DqDq).…”
Section: Discussionmentioning
confidence: 99%
“…Four major cytogenetic types of Down's syndrome are recognized (Ford, 1973 (Hamerton et al, 1963;Yunis et al, 1964;Brown et al, 1967;Atkins et al, 1968;Palmer et al, 1969;Borsgard et al, 1974). Hahnemann and Eiberg (1973) reported a kindred with a D-group marker chromosome with Down's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…D/D transloca tion was also found in autosomal abnormalities, mainly in Down's syndrome [31], reviewed by Cohen et al [5], and in Patau's syndrome [23], reviewed by T aylor et al [27], In other instances, one offspring of a D/D translocation carrier showed only the typical autosomal abnormality without the D/D trans location. This was the case in patients with 2 1-trisomy [3,13,16,29,30], and in patients with D trisomy [6,8,9], The assumption was made that D/D translocation may promote nondisjunction [I, 13].…”
Section: Discussionmentioning
confidence: 99%